Lorentz force and radiation pressure on a spherical cloak - Chen, Hongsheng (2012)
The mechanical behavior of a transformation based spherical cloak under wave illumination is derived. We show that the equatorial region of the cloak is subject to much higher stress than the polar regions, where the polar axis is defined along the wave propagation direction. These forces do not exist before transformation but stem from the squeezed electromagnetic space. The trajectory of the ray can be interpreted as a result of the recoil force that the cloak exerts upon the ray. The total radiation pressure on an ideal cloak is shown to be exactly zero, effecting a stationary cloak.